2019
DOI: 10.1177/0954408919826748
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mixing performances in microchannel with obstacles of different aspect ratios

Abstract: In this study, the mixing performance and pressure drop characteristics have been numerically analyzed for flow through rectangular microchannel with obstacles in the walls arranged in a staggered manner. Three different aspect ratios (AR) of the obstacles are considered, namely 4:1, 1:1, and 1:4. The effects of aspect ratio of the obstacles on the mixing efficiency and the pressure drop are analyzed and compared with that of the channel without obstacle. The results are presented in terms of Reynolds number (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…8−10 Generally, the mixing is divided into two categories, namely passive mixing and active mixing. 11,12 Passive mixing includes obstacles in the flow path, 13,14 adding waviness at the surfaces, 15,16 curved ribs, 17,18 grooves, 19,20 etc. Active methods include applications of external force, perturbation of fluid flow by external electric fields and electrokinetic instabilities, 21,22 electroosmotic mixing, 23 etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8−10 Generally, the mixing is divided into two categories, namely passive mixing and active mixing. 11,12 Passive mixing includes obstacles in the flow path, 13,14 adding waviness at the surfaces, 15,16 curved ribs, 17,18 grooves, 19,20 etc. Active methods include applications of external force, perturbation of fluid flow by external electric fields and electrokinetic instabilities, 21,22 electroosmotic mixing, 23 etc.…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, the development of efficient microfluidic systems has become one of the key areas of research because of its widespread applications, which include electro-micro-total analysis systems (μ-TAS), micro-electromechanical systems (MEMS), lab-on-a-chip (LOC) devices, and many more. These types of devices are extensively used for drug delivery, DNA analysis, detection of biohazardous agents, molecular separation, point-of-care diagnostic applications, etc. The efficient and rapid mixing of the two fluids is a challenging issue for such microlevel transport systems. Generally, the mixing is divided into two categories, namely passive mixing and active mixing. , Passive mixing includes obstacles in the flow path, , adding waviness at the surfaces, , curved ribs, , grooves, , etc. Active methods include applications of external force, perturbation of fluid flow by external electric fields and electrokinetic instabilities, , electroosmotic mixing, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al 36 designed and fabricated a micromixer having 64 groups of triangular barriers and reported an improved mixing efficiency with more groups of triangular barriers. Mondal et al 37 designed a micromixer with three types of obstacles and studied the effect of an aspect ratio of obstacles on mixing characteristics and pressure drop. Borgohain et al 38,39 introduced curved ribs in the T-shaped and cross T-shaped micromixer and analyzed the performance characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that trapezoidal passage provides the best performance. Mondal et al 14 estimated the pressure drop and mixing efficiency for rectangular microchannel with obstacles of different aspect ratios. A considerable enhancement in mixing efficiency was observed with incorporation of obstacles but accompanied with higher pressure drop compared to straight microchannels.…”
Section: Introductionmentioning
confidence: 99%